Scalegram Analysis of the Variability of the Polar AM Her - Andronov, I. L; Kolesnikov, S. V.; Shakhovskoy, N. M. (Одеські астрономічні публікації, 2017)
The characteristics of the brightness variations of AM Her are studied at time scales from seconds to decades by using the scalegram method proposed by Andronov (1997, As. Ap. Suppl, 125, 207). The unbiased scatter estimate increases With the filter half-Width according to a power law With an index 0.180 from 10_4 to 3000 days indicating a fractal nature of irregular variations With a low dimension of D = 0.32.